THE COMPATIBILITY OF KAHF USER COMMUNICATION IDENTITY WITH THE PERSONALITY OF MUSLIM COSMETICS BRANDS - Swasana, Muhammad Sri Mustiqa; Fithrah Ali, Dini Salmiyah (International Journal of Cultural and Social Science, 2026)
This study aims to examine how Muslim men construct and communicate their identity through the use of Kahf products, as well as examine the compatibility between user communication identity and brand personality as halal cosmetics for men. The research problem departs from the limited studies that see the consumption of men's halal cosmetics as an identity communication practice, not just consumption behavior. This study uses a qualitative approach with a case study method. Data was collected through in-depth interviews with Muslim men aged 18–35 who had experience using Kahf products, and supported by social media observations and analysis of brand promotional documents. The data was analyzed thematically interpretively. The results of the study show that the use of Kahf products is interpreted as an identity communication practice that integrates religious values, masculinity, and modernity. Halal is understood as a source of moral legitimacy that provides a sense of security and tranquility, while allowing users to express concern for appearance without conflict with religious identity. The study also found a strong correlation between user communication identity and Kahf brand personality, which reinforces the emotional attachment and symbolic meaning of the brand for urban Muslim men.